The impact of futures trade on the informational efficiency of the U.S. REIT market - Kwangwon Ahn; Hanwool Jang; Minhyuk Jeong; Sungbin Sohn (Financial Innovation)
Abstract This study examines the impact of futures trading on market efficiency and price discovery in the U.S. real estate investment trusts (REITs) market. First, we present inconclusive evidence regarding efficiency improvement in the U.S. REIT spot market following the introduction of futures trading. To investigate the interplay between spot and futures markets, we analyze their respective roles in price discovery and find that, unlike in stock and bond markets, the spot market predominantly exhibits price leadership in the U.S. REITs market, despite the growing market size of futures. We find evidence that the limited role of futures in price discovery is associated with an increase in speculative demand, which outweighs hedging pressure. These findings suggest that policymakers should carefully monitor investor trading motives in the U.S. REITs market and consider revising market regulations to enhance liquidity, ensuring that increased liquidity does not primarily result from heightened speculative demand.